JSE 30:2 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2016)
During a recent review of some issues concerning the reliability of eyewitness testimony in parapsychology, I was reminded of some fascinating episodes that I believe will interest many JSE readers. These episodes concern a familiar criticism of non-laboratory parapsychological data held, not only by parapsychological skeptics and those only casually familiar with the field, but also by many veteran psi researchers. Challenges to the reliability of eyewitness accounts typically focus on cases of physical mediumship, poltergeists, and apparitions, in which (we’re told) observers ordinarily base their reports on phenomena from darkened séance rooms, or under other poor psychological and physical conditions of observation (e.g., periods of distress or distraction, or objects moving too quickly to be observed and described reliably). Moreover, these are conditions in which observers are particularly liable to misperceive in accordance with their own biases or predispositions in favor of the paranormal. So (we’re told), eyewitness accounts in these cases should be treated with great caution at the very least, because they’re too liable to be contaminated by observer-bias in favor of the paranormal.